The philosophy and politics of Bruno Bauer - Moggach, Douglas (Cambridge University Press, 2003)
This is a comprehensive study in English of Bruno Bauer, a leading Hegelian philosopher of the 1840s. Inspired by the philosophy of Hegel, Bauer led an intellectual revolution that influenced Marx and shaped modern secular humanism. In the process he offered a republican alternative to liberalism and socialism, criticized religious and political conservatism and set out the terms for the development of modern mass and industrial society. Based on in-depth archival research this book traces the emergence of republican political thought in Germany before the revolutions of 1848. Professor Moggach examines Bauer's republicanism and his concept of infinite self-consciousness. He also explores the more disturbing aspects of Bauer's critique of modernity, such as his anti-Semitism. This book will be eagerly sought out by professionals in political philosophy, political science and intellectual history
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bauer, Bruno / 1809-1882; Bauer, Bruno -- 1809-1882; Geschichte; Republicanism; Republicanism / Germany / History; Politische Philosophie; Republikanismus; Deutschland